PENGARUH BERBAGAI JENIS BAHAN LITTER TERHADAP KUALITAS LITTER BROILER FASE FINISHER DI CLOSED HOUSE - Tiwi Metasari; Dian Septinova; Veronica Wanniatie (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The aim of this research was to 1) determine the effect of the use of rice husk, wood shavings,rice straw as litter material on litter quality for broiler during the finisher phase in closed house, 2)determine the best type of litter material on litter quality for broiler during the finisher phase in closedhouse. The duration of the research was 26 days. The research was started from 15 April to 10 May2014 in the closed house owned by PT. Rama Jaya Lampung Krawang Sari Village, the District ofNatar,Southern Lampung regency.This research was conducted using a completely randomized design (CRD) with three levels oftreatment and six replications. The treatment levels were the types of litter material (i.e. rice husk,wood shavings, chopped straw and rice). The samples were 270 broilers which were divided into 18plots. Therefore, there were 15 broilers in each plot (per square meter). The data were statisticallyanalyzed using ANOVA with 5% significance level. Duncan test with 5% significance level wasconducted for further testing should the ANOVA obtained any significant results.The results showed that(1) the use of rice husk , wood shavings and rice straw as the litter materials inclosed house showed a significant effect (P <0.05) on litter moisture content, but not significantly (P>0.05) on ammonia levels, pH, and litter temperature. (2) The litter materials of rice husk and rice strawin a closed house improved the litter